Death of a healing woman - Martin, Allana (Toronto ; New York : Worldwide, 1998)
Texana Jones, owner of a trading post in the Texas border country of Presidio County, investigates the murder of Rhea Fair, a reclusive healing woman, whose death may be linked to the killings of two close friends and the disappearance of a mysterious woman who had visited Rhea.
"A Worldwide mystery."
"A Texana Jones mystery"--Cover.
Keywords: Women detectives -- Texas; Presidio County (Tex.); Mystery fiction